Molecular Docking and Anticonvulsant Activity of Newly Synthesized Quinazoline Derivatives - Abuelizz, Hatem A. (Molecules, 2017)
A new series of quinazoline-4(3H)-ones are evaluated for anticonvulsant activity. After intraperitoneal (ip) injection to albino mice at a dose of 100 mg/kg body weight, synthesized quinazolin-4(3H)-ones (1–24) were examined in the maximal electroshock (MES) induced seizures and subcutaneous pentylenetetrazole (scPTZ) induced seizure models in mice. The Rotarod method was applied to determine the neurotoxicity. Most of the compounds displayed anticonvulsant activity in the scPTZ screen at a dose range of 0.204–0.376 mmol/mL. Out of twenty-four, compounds 8, 13 and 19 proved to be the most active with a remarkable protection (100%) against PTZ induced convulsions and four times more potent activity than ethosuximide. The structure-activity relationship concluded valuable pharmacophoric information, which was confirmed by the molecular docking studies using the target enzyme human carbon anhydrase II (HCA II). The studied quinazoline analogues suggested that the butyl substitution at position 3 has a significant effect on preventing the spread of seizure discharge and on raising the seizure threshold. However, benzyl substitution at position 3 has shown a strong anticonvulsant activity but with less seizure prevention compared to the butyl substitution.